2022
DOI: 10.1038/s41379-022-01016-8
|View full text |Cite
|
Sign up to set email alerts
|

3D analyses reveal T cells with activated nuclear features in T-cell/histiocyte-rich large B-cell lymphoma

Abstract: Nodular lymphocyte-predominant Hodgkin lymphoma (NLPHL) can show variable histological growth patterns and present remarkable overlap with T-cell/histiocyte-rich large B-cell lymphoma (THRLBCL). Previous studies suggest that NLPHL histological variants represent progression forms of NLPHL and THRLBCL transformation in aggressive disease. Since molecular studies of both lymphomas are limited due to the low number of tumor cells, the present study aimed to learn if a better understanding of these lymphomas is po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 38 publications
2
5
0
Order By: Relevance
“…On the one hand, larger tumour cell nuclei were observed in cases with variant growth patterns, possibly reflecting the presence of a higher number of genomic aberrations, mutations and overall genomic complexity 20,21 . This is in line with a previous study, in which a slightly larger nuclear area and volume in the LP cell nuclei were observed in NLPHL cases with growth pattern C 22 . On the other hand, patients with particularly large tumour cell nuclei had more limited disease supporting the hypothesis that larger nuclear size may hamper tumour cell dissemination.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…On the one hand, larger tumour cell nuclei were observed in cases with variant growth patterns, possibly reflecting the presence of a higher number of genomic aberrations, mutations and overall genomic complexity 20,21 . This is in line with a previous study, in which a slightly larger nuclear area and volume in the LP cell nuclei were observed in NLPHL cases with growth pattern C 22 . On the other hand, patients with particularly large tumour cell nuclei had more limited disease supporting the hypothesis that larger nuclear size may hamper tumour cell dissemination.…”
Section: Discussionsupporting
confidence: 90%
“…39 It has been shown that tissue macrophages in T-cell/histiocyte-rich large B-cell lymphoma express PD-L1 40 and thus probably dampen an anti-tumour cytotoxic immune response. 22 In summary, the present study for the first time elucidates tumour cell characteristics and features of the microenvironment in NLPHL in relation to the clinical presentation, expanding our understanding of the development and progression of this lymphoma entity. We have observed a correlation between both LP cell nuclear size as well as amount and interaction of PD1-positive T FH cells with clinical stages.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Higher cytotoxic and activated cytotoxic T-cells content in THRLBCL compared to NLPHL of all patterns, particularly pattern E, suggests a potential role for activation status of cytotoxic T-cells in orchestrating architectural dismantling in the transition from NLPHL to THRLBCL. Our data also con rm high CD8 content in THRLBCL, [17,48] and higher cytotoxic T-cell/monocyte interactions in THRLBCL compared with NLPHL, [49] although the functional status of cytotoxic T-cells in driving NLPHL transformation remains unknown. In addition, we show that variant NLPHL patterns, especially pattern E, has stronger cytotoxic T-cell interactions with LP cells compared to typical nodular patterns of NLPHL.…”
Section: Discussionsupporting
confidence: 64%
“…38 Additionally, the study of other diseases, such as Nodular lymphocyte-predominant Hodgkin lymphoma (NLPHL) and T-cell/histiocyte-rich large B-cell lymphoma (THRLBCL), further emphasizes the importance of nuclear 3D analyses in activated T cells. 39 Particularly, whereas 2D optical sections of T cell nuclei showed no significant enlargements, 3D volumetric measurements were necessary to show the significant differences between NLPHL and THRLBCL. We thereby anticipate that ADOPT quantification of multiparametric, immunofluorescence volumetric data of cells could not only potentially assess the functional state of T cells through nuclear measurements, but also help identify cell diseased states.…”
Section: Discussionmentioning
confidence: 98%